Different Effects of Mg and Si Doping on the Thermal Transport of Gallium Nitride - Li, Shaoxun; Yu, Linfeng; Qi, Chengdong; Du, Kun; Qin, Guangzhao; Xiong, Zhihua (Frontiers in Materials, 2021)
Mg and Si as the typical dopants for p- and n-type gallium nitride (GaN), respectively, are widely used in GaN-based photoelectric devices. The thermal transport properties play a key role in the thermal stability and lifetime of photoelectric devices, which are of significant urgency to be studied, especially for the Mg- and Si-doped GaN. In this paper, the thermal conductivities of Mg- and Si-doped GaN were investigated based on first-principles calculations and phonon Boltzmann transport equation. The thermal conductivities of Mg-doped GaN are found to be 5.11 and 4.77 W/mK for in-plane and cross-plane directions, respectively. While for the Si-doped GaN, the thermal conductivity reaches the smaller value, which are 0.41 and 0.51 W/mK for in-plane and cross-plane directions, respectively. The decrease in thermal conductivity of Mg-doped GaN is attributed to the combined effect of low group velocities of optical phonon branches and small phonon relaxation time. In contrast, the sharp decrease of the thermal conductivity of Si-doped GaN is mainly attributed to the extremely small phonon relaxation time. Besides, the contribution of acoustic and optical phonon modes to the thermal conductivity has changed after GaN being doped with Mg and Si. Further analysis from the orbital projected electronic density of states and the electron localization function indicates that the strong polarization of Mg-N and Si-N bonds and the distortion of the local structures together lead to the low thermal conductivity. Our results would provide important information for the thermal management of GaN-based photoelectric devices.